Targeting and exploiting macropinocytosis in cancer therapy - Moon, Hye-ran; Cho, Bo Kyung; Kang, Seung Hyun; Ryu, Ju Hee; Kwon, Ick Chan (Elsevier BV, 2025)
Macropinocytosis, a cellular process often hyperactivated in cancers with KRAS mutations or PTEN deficiencies, plays a crucial role in tumor survival and therapy. While inhibiting this pathway has been explored as a strategy to deprive cancer cells of essential nutrients, recent advances in nanotechnology offer an innovative approach that exploits macropinocytosis for selective drug delivery. Engineered therapeutics, including nanoparticles, peptide-drug conjugates, and macromolecule-bound drugs, leverage the elevated macropinocytic activity in tumor cells to enhance drug uptake, thereby improving treatment efficacy while minimizing off-target effects. This review provides a comprehensive examination of the molecular mechanisms regulating macropinocytosis in cancer, addressing both intrinsic factors, such as oncogenic mutations, and extrinsic influences from the tumor microenvironment. We explore both inhibition strategies and therapeutic exploitation of macropinocytosis in cancer therapy, focusing specifically on the latest innovations in engineered therapeutics designed to enhance selective drug delivery. By addressing the challenges of translating macropinocytosis-targeting therapies into clinical practice, including tumor heterogeneity and drug resistance, this review highlights how modulating macropinocytosis presents new opportunities for more effective and personalized cancer treatments.